Is Psychoanalysis a Folk Psychology? - Arminjon, Mathieu (Frontiers in Psychology, 2013)
Even as the neuro-psychoanalytic field has matured, the epistemological status of Freudian interpretations still remains problematic. As a result of the resurgence of hermeneutics, the claim has been made that psychoanalysis is an extension of folk psychology. For these “extensionists”, asking psychoanalysis to prove its interpretations would be as absurd as demanding the proofs of the scientific accuracy of folk psychology. I propose to show how Dennett’s theory of the intentional stance allows us to defend an extensionist position while sparing us certain hermeneutic difficulties. In conclusion, I will consider how Shevrin experiments could turn extensionist conceptual considerations into experimentally testable issues.